A paratoluene type artificial quartz stone resin and a preparation method thereof
Patent Information
- Application Number
- CN202611509345.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-28
- Publication Date
- 2026-10-30
AI Technical Summary
[0004]但是,上述现有制备方案主要依靠对苯二甲酸刚性芳香结构提升树脂耐热与硬度,由于分子链上芳香结构占比较高,链段柔顺性不足,树脂基体难以通过分子链形变耗散冲击能量,导致树脂整体韧性较差;在板材加工切割、开孔以及后期使用受外力冲击时,裂纹容易萌生与扩展,因此相关技术中的对苯型人造石英石树脂存在韧性不足,抗裂性能不佳的缺陷
1、本申请采用端环氧基超支化聚硅氧烷作为有机增韧组分,由于该超支化聚合物以Si-O-Si键为主链骨架,键角大且旋转能垒低,赋予分子链极高的柔顺性和极低的玻璃化转变温度,同时其端环氧基能够与聚酯主链端羧基发生开环酯化反应,以化学键形式牢固接枝于刚性聚酯主链上,使柔性硅氧烷链段成为聚酯分子的有机组成部分。在受到外力冲击时,接枝的聚硅氧烷链段能够通过大幅度的构象转变和内旋转有效耗散冲击能量;超支化聚合物特有的三维球状树形分子结构在交联网络中形成的纳米尺度自由体积空穴,在外力作用下可作为应力集中点引发银纹和剪切带,进一步消耗冲击能。在此基础上,Si-O-Si键固有的高键能确保聚硅氧烷链段的引入不会显著牺牲对苯型树脂原有的高耐热性优势,从而在保持树脂核心性能的前提下有效解决了韧性不足、抗裂性能差的缺陷。
Smart Images

Figure CN123003884A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of artificial resin technology, and more specifically, to a terephthalic synthetic quartz resin and a method for preparing the same. Background Technology
[0002] Terephthalic acid-based artificial quartz stone resin belongs to unsaturated polyester resins. It uses terephthalic acid as the main saturated diacid monomer, and synthesizes a polyester matrix through high-temperature esterification-condensation reaction with polyols and maleic anhydride. This matrix is then dissolved in styrene crosslinking monomers to obtain a liquid resin product. This type of resin possesses advantages such as high heat distortion temperature, low coefficient of thermal expansion, and high hardness. As a binder matrix, it is widely used in the vacuum-vibration-pressure molding production of artificial quartz stone and colored / dark-colored artificial quartz stone slabs. It can achieve a high proportion of inorganic filler filling, making the slabs less prone to heat warping, and offers high cost-effectiveness in the field of engineered decorative stone.
[0003] Existing technologies have published reports on the preparation process of terephthalic acid-based artificial quartz resins. For example, patent application CN115181220A discloses a method for preparing terephthalic acid-based unsaturated polyester resin and its application. This preparation method sequentially includes an esterification reaction stage, a capping stage, and a dilution stage. In the capping stage, the material is cooled to 115-135℃ and dicyclopentadiene is added. The dibasic acid components include terephthalic acid and maleic anhydride. By adopting a pre-esterification followed by capping approach, dicyclopentadiene is incorporated into the still reactive polyester long chain in a manner similar to a capping agent. This avoids premature participation of dicyclopentadiene in the chain termination reaction and prevents the decline in resin strength and other properties due to the low molecular weight of the polyester. This significantly improves the reaction efficiency of terephthalic acid and enhances the chemical corrosion resistance, heat resistance, and mechanical properties of the terephthalic acid-based unsaturated polyester resin.
[0004] However, the existing preparation methods mainly rely on the rigid aromatic structure of terephthalic acid to improve the heat resistance and hardness of the resin. Due to the high proportion of aromatic structure on the molecular chain and insufficient chain flexibility, the resin matrix is difficult to dissipate impact energy through molecular chain deformation, resulting in poor overall toughness of the resin. When the board is processed, cut, drilled, or subjected to external impact during later use, cracks are prone to initiation and propagation. Therefore, the terephthalic artificial quartz stone resin in the relevant technology has the defects of insufficient toughness and poor crack resistance. Summary of the Invention
[0005] To enhance the crack resistance of terephthalic unsaturated resin, this application provides a terephthalic artificial quartz resin and its preparation method.
[0006] This application provides a terephthalic acid-based artificial quartz stone resin, which adopts the following technical solution: A terephthalic acid-based artificial quartz stone resin comprises the following raw materials in parts by weight: Styrene 20-30 parts, ethylene glycol 10-20 parts, diethylene glycol 5-12 parts, terephthalic acid 35-45 parts, maleic anhydride 10-16 parts, terminal epoxy hyperbranched polysiloxane 2-6 parts, whisker-like nano-montmorillonite 2-8 parts, tributyl acetylacetonate 1-3 parts, polymerization inhibitor 0.1-0.6 parts, and catalyst 0.2-0.5 parts; The terminal epoxy hyperbranched polysiloxane is prepared by hydrosilylation reaction of tetramethyltetravinylcyclotetrasiloxane and hydrogen-containing silicone oil under the action of platinum catalyst, followed by end-group epoxidation capping with allyl glycidyl ether. The whisker-shaped nano-montmorillonite is prepared by transforming layered montmorillonite through acidic sol.
[0007] By adopting the above technical solution, hyperbranched polysiloxane with terminal epoxy groups and whisker-like nano-montmorillonite are introduced as synergistic toughening components, and acetylated tributyl citrate is added as a plasticizer, which fundamentally solves the technical defects of the prior art, such as high resin brittleness and poor crack resistance caused by the high proportion of rigid aromatic structure of terephthalic acid and insufficient flexibility of molecular chain segments.
[0008] First, the terminal epoxy-terminated hyperbranched polysiloxane, with its Si-O-Si bond backbone, possesses large bond angles and low rotational energy barriers, endowing the molecular chain with extremely high flexibility and a very low glass transition temperature. More importantly, the terminal epoxy groups of the hyperbranched polysiloxane can undergo ring-opening esterification with the terminal carboxyl groups of the polyester backbone during the later stages of polyester polycondensation, grafting onto the rigid polyester backbone through chemical bonds. This chemical bonding method makes the flexible siloxane segments an organic component of the polyester molecular chain. Under external impact, the grafted polysiloxane segments can effectively dissipate impact energy through significant conformational changes and internal rotation. Simultaneously, the unique three-dimensional spherical dendritic molecular structure of the hyperbranched polymer forms nanoscale free volume cavities in the crosslinking network. These microscopic cavities can act as stress concentration points under external forces, inducing crazes and shear bands, further consuming impact energy. Furthermore, the high bond energy of the Si-O-Si bond ensures that the introduction of the polysiloxane segments does not significantly sacrifice the original high heat resistance advantage of the terephthalic resin.
[0009] Secondly, the introduction of whisker-like nano-montmorillonite is another important approach to solving the crack resistance problem in this application. Unlike the layered montmorillonite used in traditional techniques, this application uses acidic sol-gel transformation treatment to induce interlayer directional curling of layered montmorillonite, forming one-dimensional whisker-like nanoparticles with a high aspect ratio. This whisker-like morphology endows montmorillonite with the ability to disperse uniformly in the resin matrix in an isotropic manner. Regardless of the direction of crack propagation, the whiskers can effectively bridge the crack surface. When the resin is subjected to external impact and microcracks are generated, the whiskers bridging the crack surface act like microscopic anchors, tightly connecting the two sides of the crack. Further crack propagation must overcome the pull-out resistance or fracture resistance of the whiskers, a process that consumes a large amount of energy. Simultaneously, the presence of whiskers also forces crack deflection and bifurcation, significantly lengthening the crack propagation path and increasing the total energy consumed during fracture. After surface grafting modification with silane coupling agent, the polymerizable double bonds introduced on the surface of the whiskers can form chemical bonds with the cross-linked network during the resin curing stage, ensuring the effective transfer of stress from the matrix to the whiskers and avoiding toughening failure caused by debonding at the two-phase interface.
[0010] Furthermore, acetylated tributyl citrate, as an environmentally friendly plasticizer, plays a supporting role in toughening and improving processing performance in this application. The ester groups in its molecular structure can form hydrogen bonds with polyester molecular chains, effectively weakening the polar interactions between molecular chains, lowering the glass transition temperature after resin curing, and increasing chain segment mobility, thereby further improving toughness without significantly reducing resin strength. Simultaneously, acetylated tributyl citrate can also reduce the viscosity of the resin system and improve the uniformity of the dispersion of whisker-like nano-montmorillonite in the matrix, creating favorable conditions for the full utilization of inorganic toughening components.
[0011] In summary, terminal epoxy-terminated hyperbranched polysiloxanes provide energy dissipation at the molecular chain segment scale, whisker-like nano-montmorillonite dissipates energy at the mesoscale through crack bridging and pinning, and tributyl acetylacetonate imparts greater freedom of movement to the chain segments at the intermolecular force level. These three functional components construct a synergistic energy dissipation network at different structural scales, maintaining the core advantages of terephthalic resins such as high heat resistance, high hardness, and low coefficient of thermal expansion while significantly improving impact resistance and crack resistance. This effectively overcomes the technical challenges of easy cracking during sheet processing, cutting, drilling, and use.
[0012] Optionally, the terminal epoxy-terminated hyperbranched polysiloxane is prepared by the following method: Tetramethyltetravinylcyclotetrasiloxane and hydrogen-containing silicone oil are mixed, and a platinum-based catalyst is added. The mixture is heated to 60-120°C under nitrogen protection and stirred for 4-12 hours to obtain a hyperbranched polysiloxane intermediate. Then, the temperature is lowered to 50-80°C, allyl glycidyl ether is added, and the reaction continues for 2-6 hours. Unreacted low-boiling substances are removed by vacuum distillation to obtain terminal epoxy hyperbranched polysiloxane.
[0013] By employing the above-mentioned technical solution, a hyperbranched polysiloxane intermediate is first synthesized through a hydrosilylation reaction between tetramethyltetravinylcyclotetrasiloxane and hydrogen-containing silicone oil under platinum catalysis. This intermediate is then capped with allyl glycidyl ether via end-group epoxidation. This preparation method has a clear route and mild reaction conditions, enabling the efficient preparation of polysiloxane toughening agents with controllable hyperbranching structures and reactive terminal epoxy groups. The hydrosilylation reaction exhibits high chemoselectivity and reaction yield, avoiding the formation of byproducts. The allyl glycidyl ether capping step quantitatively introduces reactive epoxy groups into the ends of the hyperbranched molecules, ensuring that the resulting product can form efficient chemical bonds with the terminal carboxyl groups of the polyester backbone, thereby guaranteeing that the toughening component is firmly anchored in the resin matrix through chemical bonds.
[0014] Optionally, the hydrogen content of the hydrogen-containing silicone oil is 0.8wt%-1.6wt%; the mass ratio of the tetramethyltetravinylcyclotetrasiloxane to the hydrogen-containing silicone oil is 1:(2-4).
[0015] Optionally, the platinum-based catalyst is one of chloroplatinic acid and Karstedt catalyst, and the amount of platinum-based catalyst added is 5-50 ppm of the total mass of tetramethyltetravinylcyclotetrasiloxane and hydrogen-containing silicone oil.
[0016] By adopting the above technical solution, chloroplatinic acid and Karstedt catalyst are the most mature and efficient catalytic systems for industrial hydrosilylation reactions, possessing advantages such as high catalytic activity and good reaction selectivity. Within this dosage range, the catalyst can provide a sufficient reaction rate to ensure that the hydrosilylation reaction is completed within a reasonable time window, while avoiding increased costs and product color darkening caused by excessive catalyst, which is beneficial to maintaining the appearance quality and storage stability of the final resin product.
[0017] Optionally, the amount of allyl glycidyl ether used is 10-40% of the mass of the hyperbranched polysiloxane intermediate.
[0018] Optionally, the whisker-like nano-montmorillonite is prepared using the following method: (1) Disperse sodium-based montmorillonite in deionized water and stir for 12-24 h to prepare a suspension with a solid content of 2-10 wt%. Add acidic sol to the suspension, adjust the pH to 2.0-5.0, heat to 60-90℃, stir and react for 24-72 h, centrifuge, wash with deionized water until neutral, dry, and grind to obtain modified nano-montmorillonite; (2) The modified nano-montmorillonite was dispersed in toluene, and γ-methacryloxypropyltrimethoxysilane was added. The mixture was refluxed at 80-110℃ for 4-12 h, filtered, washed, and dried to obtain whisker-like nano-montmorillonite.
[0019] By adopting the above technical solution, the preparation method systematically improves the inherent defects of traditional layered montmorillonite in polymer matrix, such as limited dispersion orientation and weak interfacial bonding. The prepared whisker-like nano-montmorillonite has both the advantages of high aspect ratio morphology and surface reactivity. It can be anchored to the cross-linked network in the form of chemical bonds during resin curing, giving full play to the crack bridging and pinning toughening effects.
[0020] Optionally, in step (1), the acidic sol is any one of silica sol, aluminum sol, or silica-alumina composite sol.
[0021] Optionally, in step (2), the mass ratio of the modified nano-montmorillonite to toluene is 1:(5-20); the amount of γ-methacryloyloxypropyltrimethoxysilane used is 5-20% of the mass of the modified nano-montmorillonite.
[0022] Optionally, the catalyst is one of monobutyltin oxide, dibutyltin oxide, and dioctyltin oxide.
[0023] By employing the above technical solution, the organotin catalyst exhibits high selectivity and excellent catalytic activity for the esterification reaction of carboxyl and hydroxyl groups, significantly shortening the esterification reaction time and reducing the reaction temperature. More importantly, compared with protic acid catalysts, organotin catalysts do not initiate side reactions of double bonds in unsaturated polyester molecular chains, avoiding adverse consequences such as gelation or broadening of molecular weight distribution, which is beneficial for synthesizing polyester prepolymers with regular molecular structures and stable crosslinking activity.
[0024] This application also provides a method for preparing terephthalic synthetic quartz resin, using the following technical solution: A method for preparing terephthalic synthetic quartz resin includes the following steps: S1. Diethylene glycol, catalyst, and terephthalic acid are added to a reactor. Under nitrogen protection, the temperature is raised to 180-190℃ and held for 0.2-0.8 hours. Then, the temperature is raised to 210-220℃ and the reaction continues until the acid value of the material is less than 5 mg KOH / g. The temperature is lowered to below 150℃, and ethylene glycol, maleic anhydride, and 40-60% polymerization inhibitor are added. The temperature is raised to 205-210℃ and the reaction continues. When the acid value drops to 50-60 mg KOH / g, vacuuming is started. The reaction continues until the acid value drops to 25-35 mg KOH / g to obtain the polyester prepolymer. S2: Cool the polyester prepolymer obtained in step S1 to 160-190℃, add terminal epoxy hyperbranched polysiloxane, and stir for 0.5-2 hours; cool to below 120℃, add whisker-like nano montmorillonite, tributyl acetyl citrate, styrene and the remaining polymerization inhibitor, and stir evenly to obtain terephthalic artificial quartz stone resin.
[0025] By adopting the above technical solution, the S1 stage employs a step-by-step feeding and gradient heating process. First, diethylene glycol and terephthalic acid undergo a preliminary esterification reaction, followed by the introduction of ethylene glycol and maleic anhydride for co-condensation. Staged vacuum operations promote the polycondensation reaction in the forward direction, resulting in a polyester prepolymer with a suitable acid value. In the S2 stage, under cooling conditions, terminally epoxy-terminated hyperbranched polysiloxanes are added sequentially for chemical grafting, along with whisker-like nano-montmorillonite, tributyl acetylacetic acid, and styrene for dilution and formulation. This method schedules the grafting reaction of the chemical toughening components after the polyester prepolymer synthesis and before styrene dilution, avoiding the adverse effects of premature addition of hyperbranched polysiloxanes on the esterification polycondensation equilibrium, while ensuring efficient ring-opening esterification of the terminal epoxy groups and polyester terminal carboxyl groups at a suitable temperature. The addition of whisker-like nano-montmorillonite in the final stage avoids potential structural damage or surface double bond thermal polymerization during high-temperature esterification, maximizing the preservation of the morphological integrity and reactivity of the inorganic toughening components. The entire preparation method is scientifically designed and controllable, which can efficiently achieve chemical bonding and uniform dispersion of various functional components in the resin matrix, ensuring a comprehensive improvement in the crack resistance of terephthalic artificial quartz resin.
[0026] In summary, this application has the following beneficial effects: 1. This application uses terminal epoxy-terminated hyperbranched polysiloxanes as organic toughening components. Because this hyperbranched polymer has a Si-O-Si bond backbone with large bond angles and low rotational energy barriers, it imparts extremely high flexibility and an extremely low glass transition temperature to the molecular chain. Simultaneously, its terminal epoxy groups can undergo ring-opening esterification reactions with the terminal carboxyl groups of the polyester backbone, firmly grafting onto the rigid polyester backbone in the form of chemical bonds, making the flexible siloxane segments an organic component of the polyester molecule. Under external impact, the grafted polysiloxane segments can effectively dissipate impact energy through significant conformational changes and internal rotation. The unique three-dimensional spherical dendritic molecular structure of the hyperbranched polymer forms nanoscale free volume cavities in the cross-linked network, which can act as stress concentration points under external force, inducing crazes and shear bands, further dissipating impact energy. Based on this, the inherent high bond energy of the Si-O-Si bond ensures that the introduction of polysiloxane segments does not significantly sacrifice the original high heat resistance advantage of the terephthalic resin, thus effectively solving the defects of insufficient toughness and poor crack resistance while maintaining the core performance of the resin.
[0027] 2. This application preferably uses whisker-shaped nano-montmorillonite as the inorganic toughening component. Through acidic sol-transformation treatment of layered montmorillonite, it undergoes interlayer directional curling to form one-dimensional whisker-shaped nanoparticles with a high aspect ratio. This differs from traditional layered montmorillonite, which tends to align in parallel within the matrix and thus struggles to comprehensively hinder crack propagation. The whisker morphology endows montmorillonite with isotropic dispersion capabilities. Regardless of the direction of crack propagation, the whiskers can effectively bridge the crack surface. When a crack forms, the whiskers spanning the crack surface act like microscopic anchors, tightly connecting the two sides of the crack. Crack propagation must overcome the pull-out resistance or fracture resistance of the whiskers, a process that consumes a significant amount of energy. Simultaneously, the whiskers force the crack to deflect and bifurcate, significantly extending the crack propagation path. After surface grafting modification with silane coupling agent, the polymerizable double bonds introduced on the surface of the whiskers can form chemical bonds with the cross-linking network during the resin curing stage, ensuring the effective transfer of stress from the matrix to the whiskers, avoiding toughening failure caused by debonding at the two-phase interface, thereby significantly improving the crack resistance of the resin.
[0028] 3. This application utilizes acetylated tributyl citrate as a plasticizer to achieve a synergistic effect with the two toughening components mentioned above, and employs a reasonable preparation method to achieve efficient composite formation of each functional component in the resin matrix. The ester groups in the acetylated tributyl citrate molecule can form hydrogen bonds with the polyester molecular chains, effectively weakening the polar interactions between molecular chains, lowering the glass transition temperature after resin curing, increasing chain segment mobility, and simultaneously reducing system viscosity and improving the dispersion uniformity of whisker-like nano-montmorillonite in the matrix. In terms of the preparation method, the chemical grafting reaction of the terminal epoxy-terminated hyperbranched polysiloxane is arranged after the synthesis of the polyester prepolymer and before styrene dilution, avoiding the adverse effects of premature addition of the hyperbranched polysiloxane on the esterification condensation equilibrium; the whisker-like nano-montmorillonite is added in the final stage, avoiding structural damage or surface double bond thermal polymerization that may occur during high-temperature esterification, maximizing the preservation of the morphological integrity and reactivity of each toughening component. End-epoxy hyperbranched polysiloxanes provide energy dissipation at the molecular chain segment scale, whisker-like nano-montmorillonite consumes energy at the mesoscale through crack bridging and pinning, and tributyl acetylacetonate imparts greater freedom of movement to the chain segments at the level of intermolecular forces. The three functional components construct a synergistic energy dissipation network from different structural scales. While maintaining the core advantages of terephthalic resin such as high heat resistance, high hardness and low coefficient of thermal expansion, it achieves a significant improvement in impact resistance and crack resistance, effectively overcoming the technical difficulties of easy cracking during plate processing, cutting, drilling and use. Attached Figure Description
[0029] Figure 1 This is the infrared spectrum of the terminal epoxy hyperbranched polysiloxane prepared in Example 1 of this application; Figure 2 This is the infrared spectrum of the terephthalic artificial quartz resin prepared in Example 3 of this application. Detailed Implementation
[0030] The present application will be further described in detail below with reference to the embodiments.
[0031] Preparation examples of epoxy-terminated hyperbranched polysiloxanes Preparation Example 1 This preparation example provides a terminal epoxy-terminated hyperbranched polysiloxane, which is prepared by the following method: Tetramethyltetravinylcyclotetrasiloxane and hydrogen-containing silicone oil were mixed at a mass ratio of 1:2, wherein the hydrogen content of the hydrogen-containing silicone oil was 0.8 wt%. Chloroplatinic acid was added as a catalyst, with the amount of chloroplatinic acid added being 5 ppm (calculated as platinum) of the total mass of tetramethyltetravinylcyclotetrasiloxane and hydrogen-containing silicone oil. The mixture was heated to 60 °C under nitrogen protection and stirred for 12 h to obtain a hyperbranched polysiloxane intermediate. The system was then cooled to 50 °C, and allyl glycidyl ether was added at 10% of the mass of the hyperbranched polysiloxane intermediate, and the reaction was continued for 6 h. After the reaction was completed, unreacted low-boiling substances were removed by vacuum distillation to obtain the terminal epoxy group hyperbranched polysiloxane.
[0032] Preparation Example 2 This preparation example provides a terminal epoxy-terminated hyperbranched polysiloxane, which is prepared by the following method: Tetramethyltetravinylcyclotetrasiloxane and hydrogen-containing silicone oil were mixed at a mass ratio of 1:3, wherein the hydrogen content of the hydrogen-containing silicone oil was 1.2 wt%. A Karstedt catalyst was added as a catalyst, with the amount of Karstedt catalyst added being 25 ppm (based on platinum) of the total mass of tetramethyltetravinylcyclotetrasiloxane and hydrogen-containing silicone oil. The mixture was heated to 90 °C under nitrogen protection and stirred for 8 h to obtain a hyperbranched polysiloxane intermediate. The system was then cooled to 65 °C, and allyl glycidyl ether was added, with the amount of allyl glycidyl ether being 25% of the mass of the hyperbranched polysiloxane intermediate. The reaction was continued for 4 h. After the reaction was completed, unreacted low-boiling substances were removed by vacuum distillation to obtain the terminal epoxy group hyperbranched polysiloxane.
[0033] Preparation Example 3 This preparation example provides a terminal epoxy-terminated hyperbranched polysiloxane, which is prepared by the following method: Tetramethyltetravinylcyclotetrasiloxane and hydrogen-containing silicone oil were mixed at a mass ratio of 1:4, wherein the hydrogen content of the hydrogen-containing silicone oil was 1.6 wt%. Chloroplatinic acid was added as a catalyst, with the amount of chloroplatinic acid added being 50 ppm (calculated as platinum) of the total mass of tetramethyltetravinylcyclotetrasiloxane and hydrogen-containing silicone oil. The mixture was heated to 120 °C under nitrogen protection and stirred for 4 h to obtain a hyperbranched polysiloxane intermediate. The system was then cooled to 80 °C, and allyl glycidyl ether was added, with the amount of allyl glycidyl ether being 40% of the mass of the hyperbranched polysiloxane intermediate. The reaction was continued for 2 h. After the reaction was completed, unreacted low-boiling substances were removed by vacuum distillation to obtain the terminal epoxy group hyperbranched polysiloxane.
[0034] Preparation example of whisker-like nano-montmorillonite Preparation Example 4 This preparation example provides a whisker-like nano-montmorillonite, which is prepared by the following method: (1) Disperse sodium-based montmorillonite in deionized water and stir for 12 h to prepare a suspension with a solid content of 2 wt%. Add silica sol to the suspension as an acidic sol, the amount of silica sol added is 10% of the mass of sodium-based montmorillonite, and adjust the pH to 2.0 with dilute hydrochloric acid. Heat to 60℃ and stir for 72 h. After the reaction is completed, centrifuge, wash with deionized water until neutral, dry, and grind to obtain modified nano-montmorillonite.
[0035] (2) The modified nano-montmorillonite was dispersed in toluene at a mass ratio of 1:5. γ-methacryloxypropyltrimethoxysilane was added, with the amount of γ-methacryloxypropyltrimethoxysilane being 5% of the mass of the modified nano-montmorillonite. The mixture was refluxed at 80°C for 12 h. After the reaction was completed, the mixture was filtered, washed with toluene, and dried to obtain whisker-like nano-montmorillonite.
[0036] Preparation Example 5 This preparation example provides a whisker-like nano-montmorillonite, which is prepared by the following method: (1) Disperse sodium-based montmorillonite in deionized water and stir for 18 h to prepare a suspension with a solid content of 6 wt%. Add aluminum sol as an acidic sol to the suspension, the amount of aluminum sol added is 30% of the mass of sodium-based montmorillonite, and adjust the pH to 3.5 with dilute hydrochloric acid. Heat to 75℃ and stir for 48 h. After the reaction is completed, centrifuge, wash with deionized water until neutral, dry, and grind to obtain modified nano-montmorillonite.
[0037] (2) The modified nano-montmorillonite was dispersed in toluene at a mass ratio of 1:12. γ-methacryloxypropyltrimethoxysilane was added, with the amount of γ-methacryloxypropyltrimethoxysilane being 12% of the mass of the modified nano-montmorillonite. The mixture was refluxed at 95°C for 8 hours. After the reaction was completed, the mixture was filtered, washed with toluene, and dried to obtain whisker-like nano-montmorillonite.
[0038] Preparation Example 6 This preparation example provides a whisker-like nano-montmorillonite, which is prepared by the following method: (1) Disperse sodium-based montmorillonite in deionized water and stir for 24 h to prepare a suspension with a solid content of 10 wt%. Add a silica-alumina composite sol as an acidic sol to the suspension. The amount of silica-alumina composite sol added is 50% of the mass of sodium-based montmorillonite. Adjust the pH to 5.0 with dilute hydrochloric acid. Heat to 90 °C and stir for 24 h. After the reaction is complete, centrifuge, wash with deionized water until neutral, dry, and grind to obtain modified nano-montmorillonite.
[0039] (2) The modified nano-montmorillonite was dispersed in toluene at a mass ratio of 1:20. γ-methacryloxypropyltrimethoxysilane was added, with the amount of γ-methacryloxypropyltrimethoxysilane being 20% of the mass of the modified nano-montmorillonite. The mixture was refluxed at 110°C for 4 hours. After the reaction was completed, the mixture was filtered, washed with toluene, and dried to obtain whisker-like nano-montmorillonite.
[0040] Example Example 1 A type of terephthalic synthetic quartz resin, the raw materials and formulation of which are shown in Table 1, wherein the terminal epoxy hyperbranched polysiloxane is selected from the terminal epoxy hyperbranched polysiloxane prepared in Preparation Example 1; the whisker-like nano-montmorillonite is selected from the whisker-like nano-montmorillonite prepared in Preparation Example 4; the polymerization inhibitor is hydroquinone; and the catalyst is monobutyltin oxide.
[0041] A method for preparing terephthalic acid-based artificial quartz resin includes the following steps: S1. Diethylene glycol, catalyst, and terephthalic acid are added to a reactor. Under nitrogen protection, the temperature is raised to 180°C and held for 0.2 hours. Then, the temperature is raised to 210°C and reacted until the acid value of the material is less than 5 mg KOH / g. The temperature is lowered to 145°C, ethylene glycol, maleic anhydride, and 40% polymerization inhibitor are added. The temperature is raised to 205°C and reacted. When the acid value drops to 50 mg KOH / g, vacuuming is started. The reaction continues until the acid value drops to 25 mg KOH / g, and polyester prepolymer is obtained. S2: Cool the polyester prepolymer obtained in step S1 to 160°C, add terminal epoxy hyperbranched polysiloxane, and stir for 0.5 h; cool to 115°C, add whisker-like nano-montmorillonite, tributyl acetyl citrate, styrene and the remaining polymerization inhibitor, and stir evenly to obtain terephthalic artificial quartz stone resin.
[0042] Example 2 A type of terephthalic acid artificial quartz resin, the raw materials and formulation of which are shown in Table 1, wherein the terminal epoxy hyperbranched polysiloxane is selected from the terminal epoxy hyperbranched polysiloxane prepared in Preparation Example 2; the whisker-like nano-montmorillonite is selected from the whisker-like nano-montmorillonite prepared in Preparation Example 5; the polymerization inhibitor is tert-butylcatechol; and the catalyst is dibutyltin oxide.
[0043] A method for preparing terephthalic acid-based artificial quartz resin includes the following steps: S1. Diethylene glycol, catalyst, and terephthalic acid are added to a reactor. Under nitrogen protection, the temperature is raised to 185°C and held for 0.5 hours. Then, the temperature is raised to 215°C and reacted until the acid value of the material is less than 5 mg KOH / g. The temperature is lowered to 140°C, ethylene glycol, maleic anhydride, and 50% of polymerization inhibitor are added. The temperature is raised to 208°C and reacted. When the acid value drops to 55 mg KOH / g, vacuuming is started. The reaction continues until the acid value drops to 30 mg KOH / g to obtain the polyester prepolymer. S2: Cool the polyester prepolymer obtained in step S1 to 175°C, add terminal epoxy hyperbranched polysiloxane, and stir for 1.5 h; cool to 110°C, add whisker-like nano-montmorillonite, tributyl acetyl citrate, styrene and the remaining polymerization inhibitor, and stir evenly to obtain terephthalic artificial quartz stone resin.
[0044] Example 3 A type of terephthalic acid artificial quartz resin, the raw materials and formulation of which are shown in Table 1, wherein the terminal epoxy hyperbranched polysiloxane is selected from the terminal epoxy hyperbranched polysiloxane prepared in Preparation Example 3; the whisker-like nano-montmorillonite is selected from the whisker-like nano-montmorillonite prepared in Preparation Example 6; the polymerization inhibitor is tert-butylcatechol; and the catalyst is dioctyltin oxide.
[0045] A method for preparing terephthalic acid-based artificial quartz resin includes the following steps: S1. Diethylene glycol, catalyst, and terephthalic acid are added to a reactor. Under nitrogen protection, the temperature is raised to 190℃ and held for 0.8 hours. Then, the temperature is raised to 220℃ and reacted until the acid value of the material is less than 5 mg KOH / g. The temperature is lowered to 145℃, ethylene glycol, maleic anhydride, and 60% of polymerization inhibitor are added. The temperature is raised to 210℃ and reacted. When the acid value drops to 60 mg KOH / g, vacuuming is started. The reaction continues until the acid value drops to 35 mg KOH / g to obtain the polyester prepolymer. S2: Cool the polyester prepolymer obtained in step S1 to 190°C, add terminal epoxy hyperbranched polysiloxane, and stir for 2 hours; cool to 115°C, add whisker-like nano-montmorillonite, tributyl acetyl citrate, styrene and the remaining polymerization inhibitor, and stir evenly to obtain terephthalic artificial quartz stone resin.
[0046] Table 1. Raw material components and proportions (g) of terephthalic synthetic quartz resin in Examples 1-3
[0047] Example 4 A type of terephthalic synthetic quartz resin, which differs from Example 3 in that: in this example, the terminal epoxy hyperbranched polysiloxane is selected from the terminal epoxy hyperbranched polysiloxane prepared in Preparation Example 2; and the whisker-like nano-montmorillonite is selected from the whisker-like nano-montmorillonite prepared in Preparation Example 4.
[0048] Example 5 A type of terephthalic synthetic quartz resin, which differs from Example 3 in that: in this example, the terminal epoxy hyperbranched polysiloxane is selected from the terminal epoxy hyperbranched polysiloxane prepared in Preparation Example 1; and the whisker-like nano-montmorillonite is selected from the whisker-like nano-montmorillonite prepared in Preparation Example 5.
[0049] Example 6 A type of terephthalic synthetic quartz resin, which differs from Example 3 in that: in this example, the catalyst is monobutyltin oxide.
[0050] Comparative Example Comparative Example 1 A terephthalic unsaturated polyester resin was prepared according to Example 1 in the patent application document with publication number CN115181220A entitled "A Method for Preparing a Terephthalic Unsaturated Polyester Resin and Its Application".
[0051] Comparative Example 2 A type of terephthalic synthetic quartz resin, which differs from Example 3 in that: no terminal epoxy hyperbranched polysiloxane was added in this comparative example.
[0052] Comparative Example 3 A type of terephthalic synthetic quartz resin, which differs from Example 3 in that: whisker-like nano-montmorillonite was not added in this comparative example.
[0053] Comparative Example 4 A type of terephthalic synthetic quartz resin, which differs from Example 3 in that: no tributyl acetylacetate was added in this comparative example.
[0054] Performance testing The resin materials of Examples 1-6 and Comparative Examples 1-4 were prepared into standard test samples and tested. The results are shown in Table 2.
[0055] Table 2 Detection Results
[0056] Based on the examples, comparative examples, and the performance test data in Table 2, it can be seen that the prior art Comparative Example 1 is a traditional terephthalic resin, which relies on the rigid structure of high proportion of terephthalic acid to ensure heat resistance and strength, but its molecular chain flexibility is poor and it has obvious brittle defects, with an impact strength of only 7.2 kJ / m. 2 With an elongation at break as low as 2.1% and a critical cracking load of only 325N, the material directly reflects the industry's technical pain point of poor toughness and easy cracking under stress in traditional terephthalic resins, which corresponds completely to the defects described in the background technology of this application.
[0057] The performance test results of Comparative Examples 2, 3, and 4 (without specific components) show that the three functional components of this application exhibit a significant synergistic toughening and crack resistance effect. Comparative Example 2 (without terminal epoxy-terminated hyperbranched polysiloxane) and Comparative Example 3 (without whisker-like nano-montmorillonite) show extremely low increases in impact strength and critical crack load, only slightly better than traditional resins. Comparative Example 4 (without tributyl acetylacetic acid) also suffers from limited toughness improvement. These results demonstrate that relying solely on a single terminal epoxy-terminated hyperbranched polysiloxane or whisker-like nano-montmorillonite cannot simultaneously achieve molecular chain flexibility optimization and microcrack suppression. Only through the synergistic combination of all three components can a complete energy dissipation system be constructed at multiple scales, solving the problems of intrinsic resin brittleness and crack propagation.
[0058] Compared to all comparative examples, the embodiments of this application show a significant gradient improvement in toughness and crack resistance, with performance continuously optimized as the amount of core modifying component added increases. In Example 3, with the optimal formulation, the impact strength reaches 17.6 kJ / m². 2 Compared with existing technologies, this technology achieves a 144% improvement, with the elongation at break increasing to 5.8%. This demonstrates that the end-epoxy hyperbranched polysiloxane, through chemical bonding grafting onto the rigid polyester backbone, effectively improves the flexibility of the terephthalic resin molecular chain. Relying on the conformational transformation of siloxane segments and the hole effect of the hyperbranched structure, it significantly enhances the resin's ability to resist impact and dissipate energy from the molecular origin, thoroughly overcoming the inherent defects of traditional resin chains being rigid and having poor deformation capabilities.
[0059] In terms of crack resistance, the critical cracking load of the plate in Example 3 reached 615N, which is 89% higher than that of the prior art, and the gain effect is extremely significant. This performance improvement is due to the unique modification advantages of whisker-like nano-montmorillonite. Compared with traditional layered montmorillonite, the one-dimensional whisker structure prepared by acid sol transformation can be uniformly dispersed isotropically in the resin matrix. Through crack bridging, pinning, deflection and whisker pull-out energy dissipation mechanism, it effectively inhibits the initiation and macroscopic propagation of microcracks. At the same time, the polymerizable double bonds grafted on the surface realize the strong bonding between the inorganic phase and the organic matrix, avoiding interface debonding failure. From the microstructure level, it solves the core problem of easy edge chipping and cracking during plate cutting, hole opening and stress.
[0060] Furthermore, the flexural strength, flexural modulus, and heat distortion temperature of each embodiment are basically the same as those of the prior art, with no significant attenuation. The auxiliary plasticizing and viscosity-reducing effects of tributyl acetylglucetate further optimize the dispersion effect of inorganic nano-components, ensure the stability of the composite modified system, and ultimately achieve a balance between high heat resistance, high toughness, and high crack resistance of styrene-type resins.
[0061] Depend on Figure 1 As can be seen, in the infrared spectrum of the terminal epoxy hyperbranched polysiloxane prepared in Example 1, 2960 cm⁻¹ -1A moderate-intensity absorption peak, attributed to saturated C-H stretching vibration, appears at 1260 cm⁻¹. -1 A sharp, strong absorption peak belonging to Si—CH3 appears at 1020-1110 cm⁻¹. -1 The presence of a very broad and strong multiple absorption band at 2160 cm⁻¹, attributed to the stretching vibration of the Si-O-Si bond, indicates that the product has a polysiloxane structure with the Si-O-Si bond as the main chain backbone. Meanwhile, the Si-H bonds in the hydrogen-containing silicone oil exhibit a strong absorption band at 2160 cm⁻¹. -1 The characteristic absorption peaks in the vicinity almost completely disappear at 1600 cm⁻¹. -1 The stretching vibration absorption of the nearby vinyl C=C bonds has also largely disappeared, indicating that the Si-H in the hydrogen-containing silicone oil has undergone sufficient hydrosilylation reaction with the vinyl groups and has been completely consumed. Furthermore, at 910 cm⁻¹... -1 and 835cm -1 The presence of characteristic absorption peaks at the locations, attributed to the C-O-C breathing vibration and the C-H out-of-plane bending vibration of the epoxy ring respectively, proves that allyl glycidyl ether has been successfully grafted onto the hyperbranched polysiloxane molecular chain via hydrosilylation. These results collectively demonstrate that Preparation Example 1 successfully prepared a terminally epoxy-terminated hyperbranched polysiloxane.
[0062] Depend on Figure 2 As can be seen from the infrared spectrum of the terephthalic synthetic quartz resin prepared in Example 3, the 1719 cm⁻¹ value is... -1 A strong absorption peak at 1575 cm⁻¹, attributed to the C=O stretching vibration of the ester carbonyl group, appears. -1 The presence of an absorption peak at 1645 cm⁻¹, attributed to the vibration of the benzene ring skeleton, indicates that terephthalic acid and the diol have undergone condensation polymerization to form a polyester backbone containing an aromatic ring structure; -1 An absorption peak at 1071 cm⁻¹ appears, attributed to the C=C stretching vibration. This unsaturated bond originates from maleic anhydride and styrene, and is retained as a reaction site for subsequent curing and crosslinking. Simultaneously, at 1071 cm⁻¹... -1 and 1039cm -1 An absorption peak at 1256 cm⁻¹ appears, attributed to the stretching vibration of the Si-O-Si bond. -1 The overlapping absorption peaks of Si-CH3 and ester CO mutually confirm that the terminal epoxy hyperbranched polysiloxane has been successfully introduced and composited into the resin matrix; 978 cm⁻¹ -1 The absorption peak at 776 cm⁻¹ belongs to the out-of-plane bending vibration of the trans-CH=CH- form. -1 731cm - The absorption peak at position ¹, attributed to the out-of-plane bending vibration of the benzene ring C—H, further confirms the presence of the unsaturated polyester and aromatic ring structure. The above characteristic peaks collectively indicate that the polyester matrix, styrene crosslinking system, and hyperbranched polysiloxane toughening component in the resin obtained in Example 3 have all been successfully constructed, and the resin preparation was successful.
[0063] This specific embodiment is merely an explanation of this application and is not intended to limit it. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but such modifications are protected by patent law as long as they fall within the scope of the claims of this application.
Claims
1. A terephthalic acid-based artificial quartz resin, characterized in that, The raw materials include the following parts by weight: Styrene 20-30 parts, ethylene glycol 10-20 parts, diethylene glycol 5-12 parts, terephthalic acid 35-45 parts, maleic anhydride 10-16 parts, terminal epoxy hyperbranched polysiloxane 2-6 parts, whisker-like nano-montmorillonite 2-8 parts, tributyl acetylacetonate 1-3 parts, polymerization inhibitor 0.1-0.6 parts, and catalyst 0.2-0.5 parts; The terminal epoxy hyperbranched polysiloxane is prepared by hydrosilylation reaction of tetramethyltetravinylcyclotetrasiloxane and hydrogen-containing silicone oil under the action of platinum catalyst, followed by end-group epoxidation capping with allyl glycidyl ether. The whisker-shaped nano-montmorillonite is prepared by transforming layered montmorillonite through acidic sol.
2. The terephthalic synthetic quartz resin according to claim 1, characterized in that, The terminal epoxy-terminated hyperbranched polysiloxane was prepared by the following method: Tetramethyltetravinylcyclotetrasiloxane and hydrogen-containing silicone oil are mixed, and a platinum-based catalyst is added. The mixture is heated to 60-120°C under nitrogen protection and stirred for 4-12 hours to obtain a hyperbranched polysiloxane intermediate. Then, the temperature is lowered to 50-80°C, allyl glycidyl ether is added, and the reaction continues for 2-6 hours. Unreacted low-boiling substances are removed by vacuum distillation to obtain terminal epoxy hyperbranched polysiloxane.
3. The terephthalic synthetic quartz resin according to claim 2, characterized in that, The hydrogen content of the hydrogen-containing silicone oil is 0.8wt%-1.6wt%; the mass ratio of the tetramethyltetravinylcyclotetrasiloxane to the hydrogen-containing silicone oil is 1:(2-4).
4. The terephthalic synthetic quartz resin according to claim 2, characterized in that, The platinum-based catalyst is one of chloroplatinic acid and Karstedt catalyst, and the amount of the platinum-based catalyst added is 5-50 ppm of the total mass of tetramethyltetravinylcyclotetrasiloxane and hydrogen-containing silicone oil.
5. The terephthalic synthetic quartz resin according to claim 2, characterized in that, The amount of allyl glycidyl ether used is 10-40% of the mass of the hyperbranched polysiloxane intermediate.
6. The terephthalic synthetic quartz resin according to claim 1, characterized in that, The whisker-like nano-montmorillonite was prepared using the following method: (1) Disperse sodium-based montmorillonite in deionized water and stir for 12-24 h to prepare a suspension with a solid content of 2-10 wt%. Add acidic sol to the suspension, adjust the pH to 2.0-5.0, heat to 60-90℃, stir and react for 24-72 h, centrifuge, wash with deionized water until neutral, dry, and grind to obtain modified nano-montmorillonite; (2) The modified nano-montmorillonite was dispersed in toluene, and γ-methacryloxypropyltrimethoxysilane was added. The mixture was refluxed at 80-110℃ for 4-12 h, filtered, washed, and dried to obtain whisker-like nano-montmorillonite.
7. The terephthalic synthetic quartz resin according to claim 6, characterized in that, In step (1), the acidic sol is any one of silica sol, aluminum sol, or silica-alumina composite sol.
8. The terephthalic synthetic quartz resin according to claim 6, characterized in that, In step (2), the mass ratio of the modified nano-montmorillonite to toluene is 1:(5-20); the amount of γ-methacryloyloxypropyltrimethoxysilane used is 5-20% of the mass of the modified nano-montmorillonite.
9. The terephthalic synthetic quartz resin according to claim 1, characterized in that, The catalyst is one of monobutyltin oxide, dibutyltin oxide, and dioctyltin oxide.
10. A method for preparing terephthalic synthetic quartz resin according to any one of claims 1-9, characterized in that, Includes the following steps: S1. Diethylene glycol, catalyst, and terephthalic acid are added to a reactor. Under nitrogen protection, the temperature is raised to 180-190℃ and held for 0.2-0.8 hours. Then, the temperature is raised to 210-220℃ and the reaction continues until the acid value of the material is less than 5 mg KOH / g. The temperature is lowered to below 150℃, and ethylene glycol, maleic anhydride, and 40-60% polymerization inhibitor are added. The temperature is raised to 205-210℃ and the reaction continues. When the acid value drops to 50-60 mg KOH / g, vacuuming is started. The reaction continues until the acid value drops to 25-35 mg KOH / g to obtain the polyester prepolymer. S2: Cool the polyester prepolymer obtained in step S1 to 160-190℃, add terminal epoxy hyperbranched polysiloxane, and stir for 0.5-2 hours; cool to below 120℃, add whisker-like nano montmorillonite, tributyl acetyl citrate, styrene and the remaining polymerization inhibitor, and stir evenly to obtain terephthalic artificial quartz stone resin.
Citation Information
Patent Citations
Preparation method and application of p-benzene type unsaturated polyester resin
CN115181220A
